Návrh marketingových aktivit konkrétní společnosti - Oulehla, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Tématem diplomové práce je vytvoření návrhu marketingových aktivit pro kavárnu a bar Limbo v Brně, který by měl vést ke zlepšení komunikačních aktivit společnosti, a následně ke zvýšení povědomí ve společnosti, popřípadě k nárůstu počtu nových zákazníků. Díky výše zmíněným důvodům je nejobsáhlejší část návrhů věnována marketingové komunikaci. Návrh vychází ze zpracovaných teoretických poznatků v první části, a především z vhodné analýzy současného stavu v části druhé.

The topic of this diploma thesis is to create a proposal for marketing activities of café and bar Limbo situated in Brno. The proposal should lead to improvement of the company’s communication skills, consequently to raise public awareness and potentially to increase the number of new customers. Therefore, the most extensive part of proposals is focused on marketing communication. The proposal is based on theoretical knowledge in the introductory part and, above all, on suitable analysis of current situation in second part of diploma thesis.
Proposal for Marketing Activities of Specific Company
Keywords: marketing služeb; marketingový mix; 7P; služba; distribuce; cena; marketingová komunikace; services marketing; marketing mix; 7P; service; distribution; price; marketing communication